1988
DOI: 10.1159/000261090
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure of Plaque to Zinc Citrate

Abstract: The effect of 3 years’ continuous exposure to dentifrices containing different levels of sodium monofluorophosphate, with or without 0.5% zinc citrate, has been investigated on plaque growth inhibition. Additionally, changes in the plaque microflora during prolonged exposure to zinc have been monitored in children with high or low caries increments. Following long-term use the inhibitory effect of zinc citrate on plaque growth was fully maintained. There was no evidence that prolonged exposure to zinc caused s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
12
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Zinc, unlike other anticalculus agents is cationic rather than anionic and can potentially operate through both of the above mechanisms [Gilbert et al, 1989], It is retained by dental plaque [Gilbert and Ingram, 1988] and inhibits its regrowth [Harrap et al, 1983[Harrap et al, ,1984Saxton et al, 1986] without disrupting the oral ecology [Jones et al, 1988] or the host immune system [Page et al, 1990]. In addition to the antiplaque effect, however, in common with a number of polyvalent metal ions and metal-ion/organic-ligand complexes [Christoffersen et al, 1987;Meyer and Thomas, 1982], zinc adsorbs onto the surface of calcium phosphate phases, inhibiting hydroxyapatite (HAP) crystal growth Zn remaining in solution, mM [Legeros et al, 1980;Meyer and Angino, 1977;Bachra and van Harskamp, 1970;Bird and Thomas, 1963], Even rela tively young plaques contain amorphous calcium phos phate crystallites which subsequently convert to HAP via brushite [Kaufmann and Kleinberg, 1973;Driessens and Verbeeck, 1989], Similarly, Brudcvold et al [1963] found that zinc was adsorbed onto the surface of both HAP and human enamel, displacing calcium.…”
mentioning
confidence: 99%
“…Zinc, unlike other anticalculus agents is cationic rather than anionic and can potentially operate through both of the above mechanisms [Gilbert et al, 1989], It is retained by dental plaque [Gilbert and Ingram, 1988] and inhibits its regrowth [Harrap et al, 1983[Harrap et al, ,1984Saxton et al, 1986] without disrupting the oral ecology [Jones et al, 1988] or the host immune system [Page et al, 1990]. In addition to the antiplaque effect, however, in common with a number of polyvalent metal ions and metal-ion/organic-ligand complexes [Christoffersen et al, 1987;Meyer and Thomas, 1982], zinc adsorbs onto the surface of calcium phosphate phases, inhibiting hydroxyapatite (HAP) crystal growth Zn remaining in solution, mM [Legeros et al, 1980;Meyer and Angino, 1977;Bachra and van Harskamp, 1970;Bird and Thomas, 1963], Even rela tively young plaques contain amorphous calcium phos phate crystallites which subsequently convert to HAP via brushite [Kaufmann and Kleinberg, 1973;Driessens and Verbeeck, 1989], Similarly, Brudcvold et al [1963] found that zinc was adsorbed onto the surface of both HAP and human enamel, displacing calcium.…”
mentioning
confidence: 99%
“…The only significant correlation that was observed was be tween total protein in stimulated saliva and mean oral hygiene scores as measured by the simplified Greene and Vermillion [1964] oral debris index.These find ings are in agreement with those reported by Grahn et al [1988] except that no correlations were seen in this study between lysozyme and gingival inflammation or immunoglobulins and dental caries. Hence results of this investigation indicate that the prolonged use of a dentifrice containing 0.5% zinc citrate, which has previously been shown to inhibit plaque formation [Jones et al, 1988], does not affect the salivary con centrations of lysozyme, lactoferrin, immunoglobulin A, total protein, nor reduce the activity of salivary peroxidase. Thus it can be concluded that a 0.5% zinc citrate dentifrice does not inhibit the non-specific sa livary antimicrobial system.…”
mentioning
confidence: 56%
“…The to tal protein concentration in stimulated saliva was significantly correlated to the oral hygiene index at the 5% level, but none of the biomolecules alone showed any significant correlation with oral health. The effect of the dentifrices used in this 3-year caries clinical trial on caries, calculus and plaque growth has been reported elsewhere [Stephen et al, 1987Jones et al, 1988]. Differences of saliva type, protein determination and subject age between this and other studies make comparisons of salivary pro tein levels difficult.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Antiplaque activity has been demonstrated both in vitro [Harrap et al, 1984] and in vivo [Fischmann et al, 1973;Skjorland et al, 1978;Saxton et al, 1986;Jones et al, 1988]. In tests for antimicrobial activity, minimum inhibitory concentrations of 0.3 mM [Oppermann et al, 1980] and 0.5 m;Vf zinc acetate [Moermann and Muehlmann, 1983] have been reported against Streptococcus mu tans in complex microbial growth media.…”
mentioning
confidence: 99%